2015
DOI: 10.1107/s2053230x15022098
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic insights into the structure–activity relationships of diazaborine enoyl-ACP reductase inhibitors

Abstract: Enoyl-ACP reductase, the last enzyme of the fatty-acid biosynthetic pathway, is the molecular target for several successful antibiotics such as the tuberculosis therapeutic isoniazid. It is currently under investigation as a narrow-spectrum antibiotic target for the treatment of several types of bacterial infections. The diazaborine family is a group of boron heterocycle-based synthetic antibacterial inhibitors known to target enoyl-ACP reductase. Development of this class of molecules has thus far focused sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…30 Our TIPA and TIPA II assays confirmed the target-specific activity of two of the four compounds ( 18c , 35b ) examined. 30 While 39 was found active against the FabI enzyme, 30 we can only found a very small zone of inhibition in TIPA II assays and have failed to observe resistant colonies.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…30 Our TIPA and TIPA II assays confirmed the target-specific activity of two of the four compounds ( 18c , 35b ) examined. 30 While 39 was found active against the FabI enzyme, 30 we can only found a very small zone of inhibition in TIPA II assays and have failed to observe resistant colonies.…”
Section: Resultssupporting
confidence: 67%
“…We and our collaborators recently reported that biochemical assays with four of the boron heterocycles showed that 14b , 18c , 35b and 39 inhibited the E. coli FabI enzyme activity. 30 More importantly, through X-ray crystallographic studies using structural models of FabI with or without 14b or 35b , we found that the sulfonyl group can be replaced with an amide or thioamide without disruption of the mode of inhibition of the inhibitors. 30 Our TIPA and TIPA II assays confirmed the target-specific activity of two of the four compounds ( 18c , 35b ) examined.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The lowest MIC values (Table ) against E. coli were provided by the DMAEMA (32 μg/mL) and DAZBMA monomers (50 μg/mL). Presumably, DAZBMA inhibits the formation of lipoprotein by entering the E. coli cell wall as it is smaller or prevents the introduction of galactose molecules into the cell wall, thus decreasing the MIC. The antibacterial activity of D 66 , with a MIC value of 750 μg/mL against E. coli , was decreased after quaternization (1QD 66 ) depending on the increase of the polarity/hydrophobicity ratio, as reported .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a decrease in the length of the organosulfonyl side chain decreases activity, while a propylsulfonyl side chain provides higher antibacterial activity . Diazaborine sulfonyl amides or thioamides inhibit enoyl‐acyl carrier protein reductase in E. coli . Only a few methods are used in the synthesis of diazaborine ring compounds.…”
Section: Introductionmentioning
confidence: 99%